2011
DOI: 10.1007/s12254-011-0249-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum uric acid and gamma-glutamyltransferase with cancer in the Vorarlberg Health Monitoring and Promotion Programme (VHM&PP) – a short review

Abstract: Th e Vorarlberg Health Monitoring and Promotion Programme (VHM&PP), based on prospectively gathered, repeated routine health examination data from a cohort of more than 175,000 adults, is one of the largest ongoing population-based risk factor surveillance programmes worldwide. Among others, the so far widely unknown associations of serum uric acid (SUA) and gamma-glutamyltransferase (GGT) with cancer were investigated. Both SUA and GGT are known to be related to the metabolic syndrome and furthermore consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Based on the concentrations, some studies reported a U-shaped or J-shaped association between SUA and cancer mortality [ 3 , 24 , 25 ]. Kua et al [ 3 ] reported a U-shaped association between SUA and all-cause and cancer mortality, with a negative association between SUA levels and mortality when the SUA levels range from 0.3 to 0.4 mmol/l, which is equivalent to 5–6.9 mg/dl The vast majority of our population (59.1 %) had SUA levels between 5 and 6.9 mg/dl; thus, our negative association is in accordance with the results of Kua et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the concentrations, some studies reported a U-shaped or J-shaped association between SUA and cancer mortality [ 3 , 24 , 25 ]. Kua et al [ 3 ] reported a U-shaped association between SUA and all-cause and cancer mortality, with a negative association between SUA levels and mortality when the SUA levels range from 0.3 to 0.4 mmol/l, which is equivalent to 5–6.9 mg/dl The vast majority of our population (59.1 %) had SUA levels between 5 and 6.9 mg/dl; thus, our negative association is in accordance with the results of Kua et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…VHM&PP is one of the world's largest population-based risk factor surveillance programmes [20] and several general relationships of body mass index, glucose, triglycerides, cholesterol, GGT, and serum uric acid with cancer have already been reported [18,[21][22][23][24]. Since 1985 all adults in the region were invited to participate and repeated routine health examinations are subsequently performed by trained physicians.…”
Section: Study Populationmentioning
confidence: 99%
“…Also, experimental models have elucidated the ability of cellular GGT to modulate crucial redox-sensitive functions, such as antioxidant/ antitoxic defences and cellular proliferative/apoptotic balance, and its role in tumour progression, invasion, and drug resistance has been proposed [9][10][11]. Furthermore, the impact of GGT on the incidence, metastasis, and recurrence of various malignancies is increasingly becoming evident [18,28,29].…”
Section: Gamma-glutamyltransferasementioning
confidence: 99%
See 1 more Smart Citation